A Translation Analysis of Idiomatic Expressions in The Webtoon Comic Entitled ‘Winter Wood' - Oktaviela, Szahara Gita (Universitas Sebelas Maret, 2023)
This study was undertaken to examine the type of idiomatic expressions, translation techniques used by translators in translating the idioms from English into Indonesian, as well as to assess the translation quality in terms of accuracy, acceptability, and readability.This research adopted a descriptive qualitative method since the result of this study were expressed in words and sentences. Documents and informants were used as data sources. The data consisted of all idiomatic expressions in the form of phrases taken from the Webtoon comic 'Winter Woods,' while the informants were three raters who assisted in classifying the types of idioms, translation technique, and assessing translation quality in terms of accuracy, acceptability, and readability. In choosing the source of data and the raters, this study used a purposive sampling technique to select a text that has a sufficient number of idioms and informants. The data were gathered using two methods: content analysis and focus group discussion.According to the research findings, there are 94 idioms in the 'Winter Woods' comic. It was found that 5 out of 6 types are found. They are phrasal verb, prepositional phrase, idiom with a verb as a keyword, idiom with a noun as a keyword, and idiom with an adjective as a keyword. It was discovered that the translators applied six different translation techniques to translate the idioms. They are idioms with similar meanings and forms, idioms with similar meanings but different forms, paraphrase, borrowing, omission of the idiom's play, and omission of the entire idiom.Phrasal verb is the dominant type of idiom found in the source language because about 80 percent of verbs in English are PV. This is the reason why PV is the dominant type of idiom found in the ‘Winter Woods’ comic. Of 6 translation techniques, paraphrase is the dominant technique used by the translators to translate phrasal verb since there is no such language structure as phrasal verb in target language. According to translation quality assesment, the translation of idiomatic expressions in ‘Winter Woodss’ comic is considered as accurate, acceptable, and readable as the translators have accurately transfered the meaning of the idioms while at the same time making it easy for the target readers to understand. Furthermore, any translation techniques are welcome in translation (in this case, idiom translation) as long as the message is fully conveyed in target language.